Return of Marxian macro-dynamics in East Asia - Ishikura, Masao; Jeong, Seongin; Li, Minqi (Emerald Publishing Limited, 2017)
The economic growth in East Asia has been believed to be the model case of the triumph of capitalism. Some progressive economists, for example, the developmental state theorists, also praised the East Asian model as the progressive alternative to neoliberal market fundamentalism, arguing that they are the outcomes of state-led development. However, with the sudden advent of the 'Lost Decade of Japan' in the 1990s, and the ensuing 'IMF Crisis' of South Korea in 1997, and now the imminent 'hard landing' of the Chinese economy, the East Asian miracle story is quickly becoming a thing of the past. East Asia has now become an epicentre of the contradictions and crisis of global capitalism. Today, deepening economic crises, exacerbation of social polarization, rising popular discontents, and escalating geopolitical tensions are common to China, Japan and Korea. Moreover, East Asia has been at the centre of global ecological contradictions. Indeed, East Asia has now become the typical place of Marxian macro-dynamics. This important and timely volume brings together experts in political economy from across the globe, to comment on the return of Marxian macro-dynamics in East Asia. The contributions explore macro-dynamics, the role of the state and hegemony in the context of transnational capitalism, and Marxian alternatives for East Asia.- Resumé vydavatel
Obsahuje index.
Keywords: kapitalismus -- Asie východní; ekonomie; capitalism -- Asia, Eastern; economics; sborníky; elektronické knihy; papers of several authors; electronic books